Adsorption of V(V), Mo(VI) and Cr(VI) Oxoanions by Chitosan–Silica Composite Synthesized by Mannich Reaction - T.M. Budnyak; V.A. Tertykh; E.S. Yanovska; D. Kołodyńska; A. Bartyzel (Adsorption Science & Technology)
Immobilization of chitosan on modified silica surface has been carried out by aminomethylation (Mannich reaction). The obtained chitosan–silica (CSS) composite was characterized by the Fourier transform infrared spectroscopy, specific surface area and pore diameter. The concentration of chitosan in the composite was determined by the thermogravimetric method. The effects of various parameters, such as pH, contact time, initial concentration of the metal on the adsorption of V(V), Mo(VI) and Cr(VI) oxoanions by the CSS composite were investigated in comparison with the initial components: chitosan, amino-containing silica and silica. The maximum adsorption capacities of composite with respect to V(V) and Mo(VI) oxoanions at pH 2.5 were 1.6 and 1.5 mmol/g, respectively, and 0.5 mmol/g towards Cr(VI) in the neutral medium.